Sexual dimorphism in reactive oxygen species production and a role for integrin α1β1 in estrogen receptor α and β expression in articular cartilage - Alicia L. Black; James Haskins; Ambra Pozzi; Andrea L. Clark (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Osteoarthritis (OA) is a debilitating disease involving cartilage degradation. A need remains for the discovery of new molecular targets in cartilage for pharmaceutical intervention of OA. One potential target is integrin α1β1 that protects against OA when it is upregulated by chondrocytes early in the disease process. Integrin α1β1 offers this protection by dampening epidermal growth factor receptor (EGFR) signaling, and its effects are more robust in females compared to males. The aim of this study, therefore, was to measure the impact of itga1 on chondrocyte EGFR activity and downstream reactive oxygen species (ROS) production in male and female mice. Furthermore, chondrocyte expression of estrogen receptor (ER) α and ERβ was measured to investigate the mechanism for sexual dimorphism in the EGFR/integrin α1β1 signaling axis. We hypothesized that integrin α1β1 would decrease ROS production and pEGFR and 3-nitrotyrosine expression, with this effect being greater in females. We further hypothesized that chondrocyte expression of ERα and ERβ would be greater in females compared to males, with a greater effect seen in itga1-null compared to wild-type mice. Materials and methods Femoral and tibial cartilage of male and female, wild-type and itga1-null mice were processed for ex vivo confocal imaging of ROS, immunohistochemical analysis of 3-nitrotyrosine, or immunofluorescence of pEGFR and ERα and ERβ. Results We show that ROS-producing chondrocytes are more abundant in female itga1-null compared to wild-type mice ex vivo; however, itga1 had limited influence on the percent of chondrocytes stained positively for 3-nitrotyrosine or pEGFR in situ. In addition, we found that itga1 influenced ERα and ERβ expression in femoral cartilage from female mice, and that ERα and ERβ were coexpressed as well as colocalized in chondrocytes. Finally, we show sexual dimorphism in ROS and 3-nitrotyrosine production, but surprisingly not in pEGFR expression. Conclusions Together these data highlight sexual dimorphism in the EGFR/integrin α1β1 signaling axis and underline the need for further investigation into the role of ERs in this biological paradigm. Understanding the molecular mechanisms underlying the development of OA is essential for the development of individualized, sex-specific treatments in this age of personalized medicine.